Gold-catalyzed heterocyclizations in alkynyl- and allenyl-β-lactams - Alcaide, Benito (Beilstein-Institut, 2011)
New gold-catalyzed methods using the β-lactam scaffold have been recently developed for the synthesis of different sized heterocycles. This overview focuses on heterocyclization reactions of allenic and alkynic β-lactams which rely on the activation of the allene and alkyne component. The mechanism as well as the regio- and stereoselectivity of the cyclizations are also discussed.